Предмет: Алгебра, автор: Аноним

помогите с решением производных.
пишите подробно

Приложения:

Ответы

Автор ответа: Artem112
0
(x^ alpha )`= alpha x^{ alpha -1}
\
(e^x)`=e^x
\
(cos x)`=-sin x
\
(ln x)`= frac{1}{x} 
\
(log_ alpha  x)`= frac{1}{xln  alpha } 
\
(ab)`=a`b+ab`
\
( frac{a}{b} )`= frac{a`b-ab`}{b^2}

y= frac{2}{x} -3 sqrt[4]{x^2}= 2x^{-1} -3x^{0.5} 
\
y`= -2x^{-2} -1.5x^{-0.5} = -frac{2}{x^2} - frac{1.5}{ sqrt{x} }

y=9( frac{x}{3} +5)=3x+45
\
y`=3

y=e^xcos x
\
y`=(e^x)`cos x+e^x(cos x)`=e^xcos x-e^xsin x=e^x(cos x-sin x)

y= frac{ln x}{1-x} 
\
y`=frac{(ln x)`(1-x)-(ln x )(1-x)`}{(1-x)^2} =frac{ frac{1}{x} (1-x)+ln x }{(1-x)^2} =frac{ frac{1}{x} -1+ln x }{(1-x)^2}

y=log_2(x^2+3)
\
y`= frac{(x^2+3)`}{(x^2+3)ln2} = frac{2x}{(x^2+3)ln2} 
\
y`(1)=  frac{2cdot 1}{(1^2+3)ln2} = frac{2}{4ln2} =frac{1}{2ln2}
Похожие вопросы
Предмет: Математика, автор: Аноним